Use of organic amendment for management of fusarium wilt of gladiolus (Bangladesh Journal of Agricultural Research, 2016)
The experiment was conducted at Horticulture Research Centre (HRC), Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during 2009-2011 following RCB design with four replications. Eight soil amendments such as Poultry refuse (5 t ha-1), Mustard oil cake (600 kg ha-1), Sesbania rostrata (5 t ha-1), Municipal waste compost (5t ha-1), BARI Trico- compost (2t ha-1), Leachate (200 ml m-2) were evaluated against Fusarium wilt of gladiolus caused by Fusarium oxysporum f. sp. gladioli under field condition. Poultry refuse was very effective in inhibiting the disease resulting maximum germination (99.98%), spike length (73.90 cm), rachis length (43.70 cm), florets spike-1 (12.63), flower sticks plot-1 (38.75) and corm plot-1 (60.23) and cormel yield ha-1 (2.51 t). Mustard oil cake, BARI Trico-compost and Sesbania rostrata compost were also effective in inhibiting the disease and resulting better spike length, rachis length, florets spike-1, flower sticks plot-1 and corm plot-1 and cormel yield.Bangladesh J. Agril. Res. 41(4): 675-684, December 2016